Protección de datos y salud mental de niños, niñas y adolescentes en el entorno digital ecuatoriano (Tema Central) - Espinosa Mogrovejo, Víctor Daniel (2026)
This paper analyzes the relationship between the right to personal data protection and the right to mental health of children and adolescents in Ecuador, in a context of increasing digitization. The study is justified to the extent that massive data collection and algorithmic design of digital platforms generate psychosocial impacts that particularly affect this group. The overall objective is to examine the applicable national and international regulatory frameworks, compare the Law on Personal Data Protection with the General Data Protection Regulation (GDPR), and identify the risks to the mental health of children and adolescents linked to the digital environment. The methodology combines a documentary analysis of legal sources with a qualitative study based on semi-structured interviews with eight experts and the analysis of recent statistical data on connectivity. The results reveal regulatory gaps, weak state supervision and regressive regulations that weaken data protection. They also identify harms such as early sexualization, anxiety, depression and digital violence. It is concluded that the absence of effective guarantees in data protection contributes to the psychosocial vulnerability of children and adolescents and that a human rights approach is required that places the best interests of children and adolescents at the center of public policies.